2017
DOI: 10.5453/jhps.52.285
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Radiation-protective Agent Research and Prospects for the Future

Abstract: Since the discovery of X-rays in 1895, radioactivity and its effects on the body have led to the issue of radiation injury. Radiation-related casualties following exposure to a lethal dose of ionizing radiation show severe acute radiation syndromes (ARS) involving bone marrow death and gastrointestinal death. ARS causes a decrease in the peripheral blood cell count and such as severe ARS, the intake of appropriate medications is the most suitable initial treatment. Therefore, the development of effective radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We previously reported that treatment with the combination of domestically approved pharmaceutical drugs (e.g. G-CSF and RP) enhances the survival of mice exposed to lethal TBI [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that treatment with the combination of domestically approved pharmaceutical drugs (e.g. G-CSF and RP) enhances the survival of mice exposed to lethal TBI [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The post-radiation treatment was performed within 2 h after TBI, and the TBI and non-TBI mice were administered different types of medications ( Table 1). The four types of medications were delivered in combinations of the following two commercially available drugs based on our previous reports [8][9][10]: recombinant human G-CSF Neutrogin® (Chugai Pharmaceutical, Tokyo, Japan) and human TPOR agonist RP (Romiplate®; Kyowa Hakko Kirin, Tokyo, Japan). G-CSF or RP was intraperitoneally administered once-daily for 3 or 4 times or once a week for up to 4 times, respectively.…”
Section: Drug Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…MCMs that can address thrombocytopenia would likely have a positive effect on ARS patients when administered alone or in combination with a G-CSF, since the duration of severe thrombocytopenia appears to correlate with death to a greater extent than that of severe neutropenia and appears to be more clinically relevant to the survival in ARS [6]. The approval of cytokine use varies by country, and GM-CSFs, interleukin-3, and thrombopoietin (TPO), which are recommended as the principal therapeutic cytokines corresponding to ARS severity by the International Atomic Energy Agency [7], are not approved in Japan. We recently found that treatment with a combination of domestically approved drugs, such as a G-CSF (Neutrogin®) and the TPO receptor (TPOR) agonist romiplostim (RP; Romiplate®), rescues mice from lethal TBI [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the combination of G-CSF and MCMs that can address thrombocytopenia can be expected to improve the pancytopenia occurs in ARS patients, since the duration of severe thrombocytopenia appears to correlate with death to a greater extent than that of severe neutropenia and appears to be more clinically relevant to the survival in ARS [ 9 ]. The approval of cytokine use varies by country, and GM-CSFs, interleukin-3, and thrombopoietin (TPO), which are recommended as the principal therapeutic cytokines corresponding to ARS severity by the International Atomic Energy Agency [ 10 ], are not approved in Japan. We recently found that treatment with a combination of approved pharmaceutical drugs, such as a G-CSF (Neutrogin ® ) and the TPO receptor (TPOR) agonist romiplostim (RP; Romiplate ® ), rescues mice from lethal TBI [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%